A quick and robust method for biomass estimation in structurally diverse vegetation - Radloff, F.; Mucina, Ladislav (2007)
Rationale: Few techniques exist for non-destructive measurement of the biomass of different co-occurring growth forms in a similar manner, and the available techniques tend to be tedious and time consuming. Aim: This paper provides an alternative technique for the measurement of components of biomass (defined in terms of growth forms) and describes an apparatus effective to perform these measurements in samples of vegetation stands up to 1.5 meter tall. Approach: The technique is based on a regression relationship between a number of probes [multiple height measurements of targeted growth forms with the help of mini disks (3 cm in diameter)] taken in a given area, and the dry biomass of these growth forms within that area. Test: We tested the method in a multi-layered shrubland composed of three major growth forms (shrub, stoloniferous grass and tussock grass) to: (1) establish how accurate the new method predicts the biomass of different plant growth forms, and (2) determine the sampling intensity necessary for reliable results. The technique proved to be very effective in terms of predicting the biomass of the respective growth forms within sample plots, even at a very low density of probes. Conclusion: The Multipoint Minidisk Meter method provides a good alternative biomass estimation method for vegetation composed of diverse growth forms, especially where sampling time is of essence. It will be especially useful to closely track changes in biomass within the same plot over time.